The energy-growth nexus: further evidence from disaggregate renewable energy sources - Kateryna Kochergina; Monteiro, H. (VII Conference of the Spanish-Portuguese Association of Resources and Environmental Economics, 2016)
This study explores the relationship between economic growth and disaggregate renewable energy sources (hydropower, biomass, wind, and solar energies) in twenty OECD countries over the period 1993-2012, a period during which the importance of renewable energy sources has grown substantially, mainly due to their role in mitigating greenhouse gas emissions. Applying recently developed panel time series techniques, we controls for unobserved heterogeneity and cross-section dependence between countries. The empirical findings suggest that there is no longrun relationship between economic growth and the different types of renewable energy. However, the results of short-run estimation show that different renewables have diverse impacts on economic growth. While biomass energy production contributes to economic growth, wind energy generation might have a negative impact on economic activity. The remaining two renewable energy categories (hydropower and solar energy) don’t appear to affect economic growth in the short run. The evidence of no interrelationship between the analyzed renewable energy sources and economic activity might be explained by their relatively low share in total energy production. Overall, the estimations results show that substantial renewable energy subsidizing doesn’t harm economic activity and so suggest continuing governmental support policies towards renewable energy deployment.